FAKTOR – FAKTOR YANG MEMPENGARUHI IBU MEMILIH KONTRASEPSI KB SUNTIK 3 BULAN DI PUSKESMAS BALOI PERMAI KOTA BATAM TAHUN 2016 - Sihombing, Sarmauli Franshisca (Universitas Batam, 2019)
The number ofacceptorsof repeated injectable contraceptivein February 2015 was in second place as many as 1,414,183. In 2015, injectablecontraceptive acceptors in Kepulauan Riau in first place with the most users, 9,250. Based on data from BatamHealth Department in 2015, there were 76,379 acceptors, 12,118 were at BaloiPermai Medical Health Center (PusatKesehatanMasyarakat, Puskesmas)in 2015, while in January 2016, theinjectable contraceptive acceptors in BaloiPermai Medical Health were 5,563 acceptors. The aim of this research was to determine the factors that affecting mothersin choosing 3 month injectable contraceptive. This study used a quantitative method with cross sectional study design using primary data by distributing questionnaires to 40 respondents. Sampling usedAccidental Sampling, research conducted from March to September 2016 analyzed using Chi Square. The results of the research category of knowledge had p-Value 0,019 which meant no relation between knowledge of mothers with mothers choosingthree month injectable contraceptive and p-Value 0,000 then there was a relationship between maternal age with mothers choose 3-month injectable contraceptives. Suggestions for mothers to continue to use birth control in order to achieve welfare in conformity with the slogan two children are enough in order to achieve welfare.